Comparing Document Object Model (DOM) and simple API for XML (SAX) in processing XML document in leave application system - Wahid, Juliana (Faculty of Information Technology Universiti Utara Malaysia, 2008)
The Extensible Markup Language (XML) consists of two Application Programming Inregace (API) i.e. Document Object Model (DOM) and Simple Application of XML(SAX). Previous research hns ued the DOM API in the Leave Application prototype. In this research, the DOM API based code that developed in the prototype will be changed to SAX API based code. The performance measurement then is carried out to evaluate the used of DOM API and SAX API in the prototype. The evaluation process took place within in each API and also combination of both APIs. From the evaluation process,it was concluded that the use of combination of SAX based code in Domino Workflow environment and DOM based code in Microsoft Exchange 2000 Server produces the lowest processing time that will increase the performance of the leave Application system.